Implementación de la Red Privada Virtual VPN en la Universidad Técnica de Cotopaxi – Extensión La Maná. - Iza Ninasunta, María Magdalena (2020)
This research project aims to facilitate communication between students, directors, teachers, employees due to the large amount of data they handle within the university is essential to have this type of technology that allows better distribution of updated information and organization of information in terms of general data of each of the members, which shows us a hierarchical tree of the directors, the mission and vision of each of the careers with their directors. For the development of this web system we analyzed the current situation of the University, together with our thesis tutor, obtaining the analysis of functional requirements which we carried out with the NinjaMock tool because it allows users to design a prototype of what will be the web system faster without the need for programming code, the tools used for development are On the server side CodeIgniter is a web development environment written in PHP and MySQL (Database Management System) language and on the client side we use boostrap is an open source multiplatform library based on (CSS and HTML) and the Debian Operating System for the installation of the application, free software tools that fit the requirements, having as a result that the members of the University community can make use of the Web System allowing access to information from any device connected to the intranet at any time you need from the three blocks that make up the university community through a username and password. The necessary tests were made to this system in order to test the correct functioning of this intranet.